2014
DOI: 10.1103/physrevb.90.075418
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonlike resonances in atomic chains: A time-dependent density-functional theory study

Abstract: We studied plasmonlike resonances in one-dimensional (1D) atomic chain systems by using time-dependent density-functional theory (TDDFT) and local density functional theory. Recent TDDFT studies have shown the coexistence of longitudinal and transverses collective plasmonlike resonances in the atomic chains of simple and noble metals. Such atomic chains contain only a few atoms. The induced polarization occurs along the atomic chain in longitudinal mode and perpendicular to the atomic chain in transverse mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
6
7
0
Order By: Relevance
“…They are also one of the simplest anisotropic structures that lead to strong and tunable resonances. Single-atom-thick chains, which have become a standard "workhorse" of quantum plasmonics [18][19][20]23,[32][33][34][35], represent the ultimate aspect ratio limit of nanorods. Their small size could lead to added tunability and novel quantum plasmonic behavior as well as aid in our understanding of how plasmons arise in larger systems within a quantum picture.…”
Section: Introductionmentioning
confidence: 99%
“…They are also one of the simplest anisotropic structures that lead to strong and tunable resonances. Single-atom-thick chains, which have become a standard "workhorse" of quantum plasmonics [18][19][20]23,[32][33][34][35], represent the ultimate aspect ratio limit of nanorods. Their small size could lead to added tunability and novel quantum plasmonic behavior as well as aid in our understanding of how plasmons arise in larger systems within a quantum picture.…”
Section: Introductionmentioning
confidence: 99%
“…It was expected that the number of energy levels around the Fermi level increased for the long carbon chain, which promoted the excitation of electrons, even for a femtosecond laser pulse with the same intensity. Meanwhile, as the number of atoms increased under electric field driving, the excited electrons formed plasm-like oscillation in linear carbon chains [14,39]. We also noted different current behaviors for two kinds of carbon chains (odd number and even number) excited by the laser field.…”
Section: Resultsmentioning
confidence: 89%
“…However, it will spend more time. Besides, the different kinds XC energy functionals, including LDA, PBE-GGA and hybrid XC energy function, have been used for other studied about linear carbon chains and performed very well [26,[44][45][46][47]. Actually, Yabana et al have demonstrated that the LDA XC energy functional provides a reasonably good approximation for many-electron ionization in strong fields [48].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations